Diretrizes e requisitos para o planejamento de obras públicas a partir da análise de processos licitatórios - Luana Maris Pedrosa Cruz (2018)
The planning process for the execution of public works must be carefully inspected and adapted to the compatibility of projects, which results in a lower index of recurrent problems in civil construction, making it important to evaluate the adequacy of management programs that assist in this process. This work consists of the applicability of the Net Project and Artemis Views management software, aimed at its implementation in the process of planning and controlling the execution of public works, in interface with Law 8666: 93. In order to achieve the good performance of the building based on the adequacy of the compatibility of projects, based on the requirements of Performance Standard ABNT NBR 15575: 2013, a survey was carried out on the planning and control of works. The research was developed based on the analysis of the application of preventive and corrective actions foreseen in the management software, aiming to comply with the legal guidelines established by Law 8666: 1993. The results obtained demonstrate the feasibility of using the Net Project software and Artemis Views, reducing material losses and efficiency in the use of public resources, thus improving the quality of the building. The analysis of the interrelationship between the Bidding Law and the Performance Standard shows that an effective integration of projects, resources and planning processes increases the performance and efficiency of the use of materials and the quality of public works